Dynamic interplay of hierarchical rank and social contexts in shaping perceived fairness - Yaner Su; Ying Zeng; Andre Aleman; Sander Martens; Pengfei Xu; Yue-jia Luo; Katharina S. Goerlich (NeuroImage)
Fairness is a core principle of social norms. Previous studies have observed that individuals’ social rank affects their perception of fairness. However, how others’ social rank influences fairness norms remains unclear. Here, we conducted two experiments using the Ultimatum Game (UG) to investigate the influence of social rank on perceived fairness in competitive versus cooperative contexts. In both experiments, participants were asked to either accept or reject different offers from proposers of varying social ranks. Experiment 1 showed that participants accepted more offers from superior than inferior proposers and rated them as fairer. Reaction times were longer for sub-fair offers, and for fair offers made by inferior players. Computational modeling further revealed greater sensitivity to unfairness from inferior versus superior proposers. Experiment 2, using the same paradigm combined with electroencephalography (EEG), replicated the behavioral pattern and additionally showed that participants accepted more fair offers and sub-fair offers from superior players than from inferior ones. However, this social rank bias disappeared for unfair offers, suggesting a trade-off between social rank and equality norms. Moreover, computational modeling further revealed that the effect of social rank on fairness sensitivity was modulated by social context. Participants were more sensitive to unfairness from inferior proposers than superior proposers in cooperative contexts, whereas this rank effect was absent in competitive settings. Additionally, participants showed higher decision consistency in the competitive context, as reflected in increased inverse temperature values. EEG results showed larger P1 amplitudes in the cooperative than in the competitive context, and more negative N170 responses to faces of superior versus inferior players. These findings suggest a temporal distinction in early neural processing, with social context encoded prior to social rank. Moreover, the medial frontal negativity (MFN) was modulated by fairness level, with sub-fair offers eliciting the largest amplitude. Importantly, late positive potential (LPP) amplitudes were enhanced for fair relative to sub-fair offers in the superior rank condition, but not in the inferior condition, showing that fairness-related neural activity was modulated by social rank. Together, these findings demonstrate a dynamic interplay between social context and hierarchical rank in shaping both fairness-related behavior and its neural correlates.